Three dimensional finite element analysis to detect stress distribution in spiral implants and surrounding bone - Matteo Danza; Annalisa Palmieri; Francesca Farinella; Giorgio Brunelli; Francesco Carinci; Ambra Girardi; Giuseppe Spinelli (Wolters Kluwer Medknow Publications, 2009)
Background:The aim of research was to study spiral family implant by finite element analysis (FEA) inserted in different bone qualities connected with abutments of different angulations. Methods:The biomechanical behaviour of 4.2 × 13 mm dental implants, connecting screw, straight and 15° and 25° angulated abutments subjected to static loads, in contact with high and poor bone qualities was evaluated by FEA. Results: The lowest stress value was found in the system composed by implants and straight abut-ments loaded with a vertical force, while the highest stress value was found in implants with 15° angulated abutment loaded with an angulated force. In addition, we found the lower the bone quality, the higher the distribution of the stress within the bone. Conclusion: Spiral family implants can be used successfully in low bone quality but applying a straight force is recommended.